Effectiveness of Cigarette Price Increases Through Excise Taxes on Smoking Prevalence: A Systematic Review - Mus’ab Mus’ab; Mardiati Nadjib (Malahayati Nursing Journal, 2026)
ABSTRACT Smoking prevalence in Indonesia remains high, while substantial evidence demonstrates that increasing cigarette prices through excise and taxation is one of the most effective economic interventions to reduce tobacco consumption. However, the magnitude of these impacts varies across countries due to differences in socioeconomic conditions, cigarette market structures, affordability levels, and prevailing fiscal policies. This study conducted a Systematic Literature Review of 12 studies from various countries to evaluate the effectiveness of cigarette price increases in reducing smoking prevalence. The findings indicate that price increases consistently lower smoking prevalence across all countries reviewed, with the strongest effects observed among adolescents and low-income populations. The highest effectiveness was found in countries with simpler excise structures and routine annual tax adjustments. For Indonesia, these findings highlight the need for stronger excise reforms, including simplifying the tax structure, implementing real annual tax increases, and eliminating low-priced cigarette segments to achieve more substantial and sustainable reductions in smoking prevalence. Keywords: Cigarette, Price Increases, Excise Taxation, Smoking Prevalence.